Analysis of achievement of the village development index 2018-2019 Kecamatan Percut Sei Tuan District Deli Serdang - Situmeang, Mahyudin; Ida Zulfida, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The development of rural communities is key in boosting the level of welfare. The village government must be able to be central to achieving this prosperity so that the village can be independent, efficient, and far from being left behind and in poverty. The purpose of this study was to examine how the Village Community Development Index in Percut Sei Tuan District was achieved. This type of research used in this research is qualitative research. The data collection techniques began with observations and interviews with informants. determination of informants using purposive sampling. Then from the results of the interview, the data processor was carried out by transcribing the results of the interview in the form of voice (audio) and writing, then data analysis was carried out, data reduction, data presentation, and conclusion drawing. The findings in this study explain that the development index of Percut Sei Tuan District is classified as good in terms of public service, governance, and infrastructure development aspects. The achievement of the village development index is inseparable from the maximum management of village funds, community participation in development, and high public trust in the government and non-governmental organizations that always support development programs. The success of village development depends on the good and bad management of village funds. Public governance has three main principles, namely accountability, transparency, and participation. The principles of village development governance can guide the management of village funds to run in an orderly manner according to the rules and these three principles. The principles of accountability, transparency, and participation require the management of village funds to comply with applicable regulations and be responsible for their implementation. The implication of this research is to improve public governance in the management of village funds. The principles of public governance can improve the quality of village government as the manager of village funds.